When "trust" becomes more or less salient for alliance performance? Contextual effects of mutual influence, international scope, and coopetition. (January 2021) - Muthusamy, Senthil Kumar; Dass, Parshotam
Extant research on strategic alliances has established that contractual controls do not provide a complete safeguard to avert an alliance failure, and that alliance governance needs to be reinforced with relational norms such as trust. However, there is scant research evidence available on whether interfirm trust can be significant under the trying contexts the alliances typically face like rivalry, power conflicts, and cultural or institutional barriers. Employing a relational exchange perspective, we examined whether the espoused positive effect of interfirm trust on alliance performance is moderated by mutual influence and coopetition between partners, and the international dimension of an alliance. Based on the survey and archival data on 223 strategic alliances, we found that interfirm trust was quite significant to alliance performance and that the link between trust and performance was more salient in alliances with high mutual influence and coopetition, whereas it was less salient and weaker in international alliances.